Levels of Application of the Strategic Process in Exporting Companies in the Northern Macroregion of Peru - Gorriti Delgado , Luz Angelica (2025)
The research analyzes the application of the strategic process in exporting companies in the northern region of Peru, with the objective of determining the levels of implementation of the strategic process in these companies. The study, with a qualitative approach and descriptive scope, was carried out in 58 companies in the departments of Tumbes, Piura, Lambayeque, La Libertad, Ancash, San Martín, Cajamarca and Amazonas. A survey validated with the Cronbach Alpha test was used to collect data. The results show that the use of Strategic Planning in these companies is higher than average and is closely linked to business management, confirming its importance as a management tool.